ANALISIS PEMAHAMAN MASYARAKAT MENGENAI PERBANKAN SYARIAH TERHADAP MINAT MENABUNG - febi febi; Muhammad Dayyan; Muhammad Riza; Amalya Ridwan (JIM: Jurnal Ilmiah Mahasiswa, 2019)
These days, sharia banking is still debatable among people. Some of them assume that profit/sharing ratio is similar to giving/return of interest rate which means that both sharia banking and conventional ones is also the same. Therefore, this study aims to investigate the people’s understanding about sharia banking, especially on saving (case study at Gampong Jawa). This is a field research by using phenomenology qualitative approach. As participants, 11 people at Gampong Jawa were interviewed to complete the data of this study. The results showed that most of them do not understand about sharia banking. However, almost of the informants were interested in saving their money at sharia banking, and only two of them were not. This shows that there are still many people who should be given an understanding of sharia banking.